The "Clubs against Drugs" program in Stockholm, Sweden: two cross-sectional surveys examining drug use among staff at licensed premises - Gripenberg Abdon Johanna; Wallin Eva; Andréasson Sven (BMC, 2011)
Abstract Background The objective of this study is to examine self-reported drug use among staff at licensed premises, types of drugs used, attitudes towards drugs, and observed drug use among guests. Results are presented from two measurement points (in 2001 and 2007/08). This study was carried out within the framework of the "Clubs against Drugs" program, which is a community-based multi-component intervention targeting licensed premises in Stockholm, Sweden. Methods Two cross-sectional surveys were conducted, the first in 2001 and the second in 2007/08. Staff at licensed premises attending server training were asked to participate in the anonymous survey. A survey was administered in a classroom setting and consisted of four sections: 1) demographics, 2) respondents' own drug use experience, 3) respondents' attitudes towards drug use, and 4) observed drug use among guests at licensed premises. Results Data were collected from 446 staff in 2001 and 677 staff in 2007/08. The four most commonly used drugs among staff were cannabis, cocaine, amphetamine, and ecstasy. The highest rates of drug use were reported by staff in the two youngest age groups, i.e., those younger than 25 and those between the ages of 25 and 29. In 2007/08 staff reported significantly lower rates of drug use than staff in 2001. Last year drug use for the sample in 2007/08 was 19% compared to 27% for the 2001 sample. While drug-using staff compared to non drug-using staff reported more observations of drug use among guests, they were less inclined to intervene. Overall, staff reported restrictive attitudes towards drugs. Conclusions The prevalence of life-time and last year drug use among staff at licensed premises is high compared to the general population in Sweden. Lower rates of self-reported drug use among staff were reported in 2007/08. The results of this study highlight that staff at licensed premises represent an important target population in club drug prevention programs.